Molecular Profiling of Pediatric and Adult Glioblastoma: A Spotlight on Mismatch Repair Proteins. Issue 4 (19th November 2020) - Gestrich, Catherine K; Jajosky, Audrey N; Elliott, Robin; Stearns, Duncan; Sadri, Navid; Cohen, Mark L; Couce, Marta E
Abstract: Objectives: Although glioblastoma (GBM) is rare in the pediatric population, it is the most common cause of death among children with central nervous system neoplasms. Recent molecular profiling of these neoplasms has demonstrated distinct differences in comparison to their adult counterparts. Moreover, many pediatric GBMs occur within the context of cancer predisposition syndromes, such as constitutional mismatch repair deficiency syndrome (CMMRD). Children with CMMRD who develop GBM exhibit a high tumor mutational burden and may benefit from treatment with immune checkpoint inhibitors. Methods: We performed next-generation sequencing and immunohistochemistry for mismatch repair proteins in our cohort of pediatric and adult GBMs to further characterize the molecular profiles of these groups. Results: We examined a total of 11 pediatric and 11 adult GBMs. Pediatric patients had a higher number of alterations compared to their adult counterparts. They also had a higher frequency of alterations in the mismatch repair genes, which can be detected by immunohistochemistry (IHC). We also identified one pediatric patient with CMMRD syndrome. Conclusions: Our study highlighted the distinct molecular differences between pediatric and adult GBM. We also demonstrated that pediatric patients have a higher frequency of alterations in the mismatch repair genes, which may render them susceptible to treatment with immune checkpoint inhibitors. These alterations can be detected using routine IHC and should be performed on all pediatric GBM.